Immortelles: Literary, Botanical, and National Memories - Marler-Kennedy, Kara (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
AbstractThis article examines the history of the popular immortelle flower and its role in aesthetic and material culture from the period of 1780–1930 in England and the United States. The flower was often used and referred to in funerary and literary productions as a symbol of longevity, resurrection, and, of course, immortality (as its name suggests). Exploring the flower’s once far-reaching span reveals a rich memorializing tendency during this period that sought to challenge the anxieties of modernity.